Unusual presentation of recurrent subtrochanteric non-union in a patient with hip arthrodesis: A case report. (December 2018) - Pascarella, R.; Cerbasi, S.; Maresca, A.; Sangiovanni, P.; Fantasia, R.
Abstract: This case report describes the management and therapeutic solution for the treatment of subtrochanteric non-union in a patient with hip arthrodesis. Two techniques can be used in the treatment of these non-unions: a closed intramedullary nailing or an open technique with plate, preferably carried out together with cortical bone graft. The surgical technique varies depending on the fixation method used for the initial treatment of the fracture and on the characteristics of the non-union. We report an unusual case of a patient who started her long clinical history more than 40 years ago with a septic arthritis of the hip healed in arthrodesis. 35 years later, after having undergone various surgeries, she fractured the proximal femur, which had to be operated seven times before reaching healing. Satisfactory outcomes were finally obtained. Arthrodesis proved to be the main cause of failed healing and of the recurrent non-union.